Sidonia, the Sorceress : the Supposed Destroyer of the Whole Reigning Ducal House of Pomerania Volume 1 - Meinhold, Wilhelm, 1797-1851 (Salt Lake City, UT : Project Gutenberg, 2004)
"Sidonia, the Sorceress: the Supposed Destroyer of the Whole Reigning Ducal House of Pomerania" by William Meinhold is a fictional novel written in the late 19th century. It follows the tumultuous life of Sidonia von Bork, who is accused of witchcraft and is blamed for the misfortunes of the ducal family of Pomerania, including causing sterility in their line. The book explores themes of power, supernatural beliefs, and societal fears about witchcraft. The opening of the novel sets the historical context by detailing the infamous trial and execution of Sidonia von Bork, a noblewoman accused of sorcery and witchcraft in 1620. It begins with a preface by Dr. Theodore Plönnies, offering insights into Sidonia's early life and education, underlining her contentious relationships with the noble class, particularly her father Otto von Bork. Full of intrigue, the early chapters depict the circumstances surrounding her rise to notoriety, her interactions at the court, and hints at the jealousy and revenge that will define her fate. The narrative portrays a society steeped in superstition and the consequences of a woman who dares to confront the social norms of her time. (This is an automatically generated summary.)
Release date is 2004-10-01
Produced by Steve Schulze, Charles Franks and the Online Distributed Proofreading Team. This file was produced from images generously made available by the CWRU Preservation Department Digital Library
Keywords: Witchcraft -- Pomerania (Poland and Germany)